Effect of conventional and rolled cigarette smoke on the colour of artificial teeth and effectiveness of hygiene protocols in removing pigmentation - An in vitro study - Graziele Cristina Alvim; Gabriella Rodovalho Paiva; Carla Cecilia Alandia-Román; César P Lepri; Denise T De Castro (Wolters Kluwer Medknow Publications, 2022)
Context: Artificial teeth are widely used in oral rehabilitation. Despite the benefits, they are more susceptible to colour changes, causing aesthetic problems. Aims: To evaluate the effect of conventional cigarette and straw smoke on the colour of artificial teeth and the effectiveness of hygiene protocols in removing pigmentation. Material and Methods: Acrylic resin incisors were divided into two groups (n = 50): Exposed to conventional cigarette and straw smoke. Regarding the effectiveness of hygiene protocols, the teeth were divided into ten subgroups with predetermined immersion times. The colour was measured with a colorimeter. The CIE values L* a* b* were recorded before and after exposure to smoke and after hygiene protocols. Statistical analysis used T-test of independent samples and two-way ANOVA with Bonferroni post-test (α = 0.05). Results: Conventional (16.16 ± 1.65) and straw (16.29 ± 1.95) cigarettes provided clinically unacceptable ΔE values, with no significant difference between them (P = 0.719). Conventional cigarettes promoted less luminosity (ΔL = -12.68 ± 1.28) (P < 0.001) and straw greater tendency to yellow (Δb = 11.00 ± 1.46) (P < 0.001). The hygiene protocols influenced the ΔE, ΔL, and Δb of the samples, depending on the type of smoke (P < 0.05). Conclusions: The conventional and rolled cigarette smoke promote an unacceptable colour change in artificial teeth. Hygiene protocols with the use of brushing, in isolation or in association with chemical solutions are more effective in removing pigmentation caused by both types of cigarettes compared to only the chemical solution.